Synthesis of Cerium Oxide Nanoparticles and its Behavior under Aqueous Environmental Factors - Syazani Azaim, Eddie Halim (University Malaysia Sarawak, 2024)
Cerium oxide, CeO2 nanoparticles (NPs) are metal oxide NPs used in various applications such as in fuel oxidation catalysis, solar-driven energy production and as fuel additives. However, CeO2 NPs have been reported to behave differently when released to the environment due to the difference in pH, ionic strength (IS) and concentration of natural organic matter (NOM). In this study, CeO2 NPs was synthesized using the hydrothermal method at 70 ℃ using cerium nitrate hexahydrate, Ce(NO3)3 • 6 H2O and sodium hydroxide, NaOH as the precursors while deionized water was used as the solvent. The synthesized CeO2 NPs were characterized using field emission scanning electron microscope (FESEM), transmission electron microscope (TEM), energy dispersive X-ray (EDX), ultraviolet visible (UV-Vis) spectrometer, Fourier transform infrared (FTIR) spectroscopy, X-Ray Diffraction (XRD) and Brunauer -Emmett-Teller (BET) method. High specific surface area of 185 m2/g, average particle size of (TEM: 3.5 nm, BET: 4.5 nm) and crystallite size of 3.05 nm was determined through the characterization process. The absorption peak at 305 nm and 447.20 cm-1 for UV-Vis and FTIR analyses respectively confirmed the presence of CeO2 NPs. The absence of impurities from EDX and XRD diffraction pattern proved that the synthesized CeO2 NPs was of high purity. The adsorption of HA on CeO2 NPs was performed using UVVis to measure the amount of HA adsorbed at the absorbance of 254 nm. Higher adsorption was observed at acidic pH compared to the alkaline pH and the adsorption was following the Pseudo-second order and Langmuir isotherm. The dissolution of CeO2 NPs was studied by measuring the dissolved Ce4+ using inductively coupled plasma-optical emission spectroscopy (ICP-OES). Increased in ionic concentration and pH was found to decrease the dissolution of CeO2 NPs while increased in HA concentration and pH resulted into a greater stability of CeO2 NPs.